COMPARATIVE STUDY OF HYBRID CATAMARAN VERSUS DIESEL MONOHULL BOAT AS FERRY FOR SHORT DISTANCE ROUTES. - M, Ferry (Diponegoro University, 2013)
The increasing of fossil’s fuel prices and environmental awareness urges engineers try to hybrid diesel with green energy such as solar energy. Through photovoltaic cells, solar energy is converted into electricity that could power the electric motors as the prime mover at a catamaran that has more slimmer and shallower cross-section area than single hull boat of an equivalent displacement has less draught, more deck area and more stable.. Electric motor maintains high efficiency over a wide range of loads and speeds has a small weight and need low maintenance and repair cost compared to diesel engines or outboard motors. At countries like Malaysia and Indonesia where solar energy is available during average six to seven hours a day is a quite good time range to charge the batteries until reach its full capacity, but when solar radiation is not available the battery charging is taken over by diesel generator. Such hybrid system is efficiently to be used for catamaran boat on rivers, between ports at coastal area and between closed islands due to its less the operational cost, maintenance cost and less carbon emission compare with fully diesel system, hence this is a more environmental friendly system.